Genetic effects of iron levels on liver injury and risk of liver diseases: A two-sample Mendelian randomization analysis - Wang, Kai; Yang, Fangkun; Zhang, Pengcheng; Yang, Yang; Jiang, Li (Frontiers in Nutrition, 2022)
Background and aims: Although iron homeostasis has been associated with liver function in many observational studies, the causality in this relationship remains unclear. By using Mendelian Randomization analyses, we aimed to evaluate the genetic effects of increased systemic iron levels on the risk of liver injury and various liver diseases. Moreover, in light of the sex-dependent iron regulation in human beings, we further estimated the sex-specific effect of iron levels in liver diseases. Methods: Independent single nucleotide polymorphisms associated with systemic iron status (including four indicators) at the genome-wide significance level from the Genetics of Iron Status (GIS) Consortium were selected as instrumental variables. Summary data for six liver function biomarkers and five liver diseases were obtained from the UK Biobank, the Estonian Biobank, the eMERGE network, and FinnGen consortium. Mendelian Randomization assessment of the effect of iron on liver function and liver diseases was conducted. Results: Genetically predicted iron levels were positively and significantly associated with an increased risk of different dimensions of liver injury. Furthermore, increased iron status posed hazardous effects on non-alcoholic fatty liver disease, alcoholic liver disease, and liver fibrosis/ cirrhosis. Sex-stratified analyses indicated that the hepatoxic role of iron might exist in NAFLD and liver fibrosis/ cirrhosis development among men. No significantly causal relationship was found between iron status and viral hepatitis. Conclusion: Our study adds to current knowledge on the genetic role of iron in the risk of liver injury and related liver diseases, which provides clinical and public health implications for liver disease prevention as iron status can be modified.